Bioactive Materials for Soft Tissue Regeneration - Chang, Jiang; Chang, Jiang; Li, Bin; Li, Bin (Academic Press, 2024)
This is a follow up of the authors' previous book entitled "Bioactive materials for bone regeneration. Generally speaking, human tissue can be classified as hard tissue such as bone and soft tissue such as skin, mussel, tendon, blood vessel, nerve etc. and including important organs such as heart, liver, lung. Regenerative medicine is dealing with both hard tissue and soft tissue regeneration and is one of the most important part of the modern medicine with significant clinical needs including general surgery, plastic surgery, burn and wound healing, cardiovascular disease treatments. Based on the authors' previous research and review of the international advances in hard tissue regeneration, this book focuses on the hard tissue regeneration using bioactive materials. It covers biomaterials for entire human tissue regeneration, which is key important for research and development in the field of biomedical engineering and the medical device industry. This book will give readers a comprehensive review of principal and the most updated advances of the research in bioactive materials for soft tissue repair and regeneration, and perspectives for the future directions of the research and development in this field. - Covers recent development of bioactive materials for soft tissue regeneration - Provides basic principles for design of bioactive materials for tissue regeneration - Includes future perspectives surrounding the development of bioactive materials that will be valuable to the readers